THE SECOND LANGUAGE ACQUISITION OF ENGLISH CONCORD ( - Hendro Setiawan Husada (TEFLIN, 2007)
This study investigated the types and causes of errors in learning the English concord among Indonesian students of English. The errors would be focused on the studentsÃ¢â¬â¢ interlingual (mother tongue) as well as intralingual (learning strategies) interference. The data were all collected from the students at Satya Wacana Christian University, Indonesia. Two research questions were answered: 1) between interlingual and intralingual errors, which one did the participants make more in learning English concord? 2) Among intralingual errors, which source of errors was the most evident? Fifteen students (n = 15) participated in this study. In regard to the data collection and analysis, I used the steps suggested by Corder (1974, in Ellis and Barkhuizen, 2005). The results of this study suggest that the intralingual errors were more significant than interlingual ones in the acquisition of the concord. The results were in line with some of the previous findings found by Bataineh (2005), Chan (2004), Duskova (1983), Lim (2003), and Richards (1983). They also supported the claim in the field of SLA that acquisition of a foreign language is determined by the nature of the language that the learners are learning, rather than through contrast between the learnersÃ¢â¬â¢ first language and the target language.